The effect of quality factors of hospital information systems on patient satisfaction - Jad, Kamilia Abdulmutalib Mohamed; Zainol, Zuraidah (Ifma Publishing, 2022)
Hospital information systems (HIS) have brought significant changes in the way hospitals communicate with patients and add great value to the medical services provided by modern. Despite HIS long implementation in the public hospitals in the UAE, little is known about the quality aspects of HIS on patients. Accordingly, this study addresses this gap and assesses the effect of system quality, service quality, and information quality of HIS on patients’ satisfaction. This study adopted a quantitative approach. The sample consists of 500 patients at public hospitals in Al-Sharjah city. Respondents were selected using a systematic sampling technique. Data were collected using the questionnaire and analyzed using Structural Equation Modeling. The results reveal that the quality attributes of HIS i.e. system quality, service quality, and information quality, have a significant effect on patients’ satisfaction. Notably, these attributes are important measures of the success of every information system. Hence, HIS should be carefully designed to ensure these measures are well delivered for the users of these systems as well as hospital staff.